ANALISIS KEPUASAN ANGGOTA KOPERASI TERHADAP KUALITAS PELAYANAN PADA KOPERASI CREDIT UNION SUMBER SEJAHTERA KALIMANTAN SELATAN - Isra Ul Huda; Jhony Fahrin Sapar (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Cooperative which means a joint venture (Anoraga and Widiyanti, 1997:38-39). Cooperatives are people's economic institutions that encourage the people's economy to increase people's prosperity. Therefore, the focus of cooperatives is not only on products and services but also on their production, human resources, and the environment. Member satisfaction is the main factor that can make switching to another financial institution. Member satisfaction is one of the main goals of every institution. In this case, an important factor contributing to member satisfaction is service quality, which is recognized as the most important factor in member satisfaction. Member satisfaction depends on the quality of service desired. Based on the background of the problem, the formulation of the research problem is How is the Analysis of Cooperative Member Satisfaction on Service Quality at the Sumber Sejahtera Credit Union Cooperative, South Kalimantan?. The purpose of this study is to determine the satisfaction of cooperative members on service quality at the Sumber Sejahtera Credit Union Cooperative, South Kalimantan. The type of research used by the researcher is descriptive qualitative. According to Sugiyono (2016: 9) qualitative research methods are research methods used to examine the condition of natural objects where the researcher is the key instrument. In this study, the author uses an analytical technique, namely the customer satisfaction index (CSI). And the technique used in data collection is a questionnaire. The feasibility and reliability of the questionnaire will be measured using the validity and reliability test of the questionnaire, which data collection is online using the google form media. The study entitled